Structural, electronic and kinetics on organometallic intercalates of metal dichalcogenides - Wong, H; Wong, Heng-Vee (1993)
Large single crystals of the metal dichalcogenide hosts ZrS2 and 811X2 (X = S, Se) have been successfully intercalated with a variety of organometallic guests {C0(η-C5H5)2, CO(η-C5H4CH3)2, Mo(η-C6H6)2, Mo(η-C7H7)(η-C5H5), W(η-C7H7)(η-C5H5), Ti(η-C8H8)(η-C5H5)}. The structural and electronic properties of these materials have been studied, as well as the intercalation kinetics of these organometallic species into the tin dichalcogenides. X-ray and neutron diffraction experiments have been used to obtain 001 reflections in order to obtain a one-dimensional profile of electron and neutron scattering in these disordered layered materials (Chapter Two). Refinement of the data shows that for all the organometallic guests, the majority of the intercalant adopts an orientation in which the principal molecular axis lies parallel to the layer planes of the host. These findings are confirmed by 2H NMR spectroscopy on single crystals of deuterated cobaltocene intercalates of ZrS2 and SnSe2, where it has been shown that rapid C5, but not C2, rotation of the metallocene occurs in the interlamellar van der Waals space. To study the electronic properties of these intercalates, electrical resistivity and magnetic susceptibility measurements have been performed (Chapter Three). An apparatus has been built to measure the resistivity of these crystal intercalates down to 4.2K. The resistivity measurements show that intercalation of various organometallic complexes confers metallic properties upon ZrS2 while SnS2{Co(η-C5H5)2} 0.3 becomes a superconductor with a Tc of 8.3K. The magnetic susceptbility measurements confirm the presence of guest-host charge transfer. Estimates of its extent, as well as the magnitude of the Pauli susceptibility in these intercalates, have been attempted. Studies on the rate and mechanism for the intercalation of cobaltocene into the disulfides and diselenides of tin have been performed (Chapter Four). An apparatus has been designed and constructed for in situ diffraction using synchrotron X-rays in order to monitor the progress of these rapid intercalation reactions. The results indicate that the rate of intercalation of cobaltocene into the tin dichalcogenides is very much dependent on the solvent used, being significantly faster in dimethoxyethane than in toluene. Analyses of the kinetic rate expressions for the tin dichalcogenide intercalation in dimethoxyethane suggests that diffusion of cobaltocene molecules into the interlamellar space constitutes the rate limiting step. The choice of solvent also dramatically affects the mechanism of the intercalation. When a solution of cobaltocene in dimethoxyethane is used, the host transforms directly to the final product but in toluene, staged intermediates are observed during the intercalation process. The apparatus and techniques that have been developed for the in situ kinetics experiments are general and permit dynamic structural transformations in air- and moisture-sensitive suspensions of solids to be effectively studied.